Changing time - Ortiz, Cristian (Journal of the Foot & Ankle, 2020)
Any forecast of the pandemic dynamics has proven to be far away from what has really happened, particularly in South America. In most of our countries, we are still struggling with what has been called the first wave. The virus has impacted not only our health status but also every aspect of our lives, including our daily work. Spending less time in the operating room has a positive side that each one has experienced differently. It has provided the opportunity for more quality time with the family and an understanding of how vulnerable we all are, how complicated politics and economic decisions are, and how important the way we all communicate and share experiences is. Most of us have seen our workplaces becoming busy with an increasing number of patients, which has led us to cancel any elective surgery and stay home in isolation. This difficult time we are going through has allowed us to think about our purpose in life, especially as physicians. We have been forced to develop new ways of teaching medicine, researching, and even practicing medicine. Most importantly, difficult times require that we learn a new way of living. This has led us to reflect on the importance of research and on how important it is that all of us give our best for our patients. Treating patients well impels us to be informed, to be updated about new knowledge, and to practice our skills while continuously looking for answers. The virtuous circle to be a good doctor should always include clinical practice, medical education, and research. When I was asked to write this editorial, one thought immediately came to my mind: how easily some journalists and public figures get into trouble after making a comment, writing an editorial, or even after publishing a post on social media. A recent example is what happened to J. K. Rowling, the famous author of the Harry Potter series. Last December, she tweeted her support for Maya Forstater, who was fired for what were deemed “transphobic” tweets. Rowling has received accusations and threats from trans activists and many worldwide famous people. A single ‘like’ was deemed evidence of ‘wrongthink’, and a persistent level of harassment began. The world has definitely changed, and everyone’s comments and behaviors are completely public. We should not be afraid to speak up and express our opinion, we should not be stopped by the fear of having people against us. As physicians, we are all exposed by expressing our medical opinion every day in the office, in a meeting, or even in a remote setting. Every decision and opinion should be based on evidence, but they will inevitably include our personal background-which is a mix of knowledge and personal life experience. Hopefully, these opinions will always express our genuine interest in the patients and their families as our main focus. As I get older, I pay more attention to the basis of my daily practice, which begins with proper information provided by good sources of medical education such as this journal. However, acquiring reliable information is just the beginning of the path toward good medical practice. The remainder of the path-the most important part of it-must be trodden by a human being truly interested in doing the best for his/ her patients every day. It has always amazed me that everyone who I admire as a physician is, at the same time, a professor, a researcher, and an amazing human being. This journal is the result of the efforts of a group of people who are truly committed to learning, teaching, and investigating, thus producing friendly feedback and updated knowledge.